Géopolitique de l’austérité - Mutations de l’espace politique et renforcement des clivages au Royaume-Uni depuis la crise de 2008 - Mark Bailoni (L'Espace Politique)
The United Kingdom is confronted with a geopolitics of austerity, following the 2008 crisis and governments’ policies. Several interdependent issues, sometimes pre-existing, are then strengthened and reconfigured: emergence of a protest vote, rise of nationalisms and regionalisms, Brexit, local rivalries or claims for decentralisation. This geopolitics of austerity reveals the fault lines of the United Kingdom, a multi-nation state, whose institutional stability and unity seems weakened. After a multiscalar analysis of the rise of protest votes since 2008, this paper examines the strategies of resistance to the austerity policy in specific territories, especially Scotland and Northern England.